ZFP148 (Zinc-Finger Protein 148) Binds Cooperatively With NF-1 (Neurofibromin 1) to Inhibit Smooth Muscle Marker Gene Expression During Abdominal Aortic Aneurysm Formation. Issue 1 (January 2019) - Salmon, Morgan; Schaheen, Basil; Spinosa, Michael; Montgomery, William; Pope, Nicolas H.; Davis, John P.; Johnston, William F.; Sharma, Ashish K.; Owens, Gary K.; Merchant, Juanita L.; Zehner, Zendra E.; Upchurch, Gilbert R.; et al.
Abstract : Objective—: The goal of this study was to determine the role of ZFP148 (zinc-finger protein 148) in aneurysm formation. Approach and Results—: ZFP148 mRNA expression increased at day 3, 7, 14, 21, and 28 after during abdominal aortic aneurysm formation in C57BL/6 mice. Loss of ZFP148 conferred abdominal aortic aneurysm protection using ERTCre+ ZFP148 flx/flx mice. In a third set of experiments, smooth muscle-specific loss of ZFP148 alleles resulted in progressively greater protection using novel transgenic mice (MYH [myosin heavy chain 11] Cre+ flx/flx, flx/wt, and wt/wt). Elastin degradation, LGAL3, and neutrophil staining were significantly attenuated, while α-actin staining was increased in ZFP148 knockout mice. Results were verified in total cell ZFP148 and smooth muscle-specific knockout mice using an angiotensin II model. ZFP148 smooth muscle-specific conditional mice demonstrated increased proliferation and ZFP148 was shown to bind to the p21 promoter during abdominal aortic aneurysm formation. ZFP148 smooth muscle-specific conditional knockout mice also demonstrated decreased apoptosis as measured by decreased cleaved caspase-3 staining. ZFP148 bound smooth muscle marker genes via chromatin immunoprecipitation analysis mediated by NF-1 (neurofibromin 1) promote histone H3K4 deacetylation via histone deacetylase 5. Transient transfections and chromatin immunoprecipitation analyses demonstrated that NF-1 was required for ZFP148 protein binding to smooth muscle marker genes promoters during aneurysm formation. Elimination of NF-1 using shRNA approaches demonstrated that NF-1 is required for binding and elimination of NF-1 increased BRG1 recruitment, the ATPase subunit of the SWI/SWF complex, and increased histone acetylation. Conclusions—: ZFP148 plays a critical role in multiple murine models of aneurysm formation. These results suggest that ZFP148 is important in the regulation of proliferation, smooth muscle gene downregulation, and apoptosis in aneurysm development. Abstract : Supplemental Digital Content is available in the text.